Identification of Drug Resistant Candida auris - Kordalewska, Milena; Perlin, David S. (Frontiers in Microbiology, 2019)
Candida auris is a multidrug resistant yeast, recognized as a cause of invasive infections and health care associated outbreaks around the world. C. auris is of great public health concern, due to its propensity for drug resistance, mode and pace of its transmission, and the possibility that biologic and epidemiologic factors could exacerbate worldwide emergence of C. auris infections. Currently, outbreak response is complicated by limited treatment options and inadequate disinfection strategies, as well as by issues (misidentification, long turnaround time) associated with application of commonly used diagnostic tools. Misdiagnosis of C. auris is common since many diagnostic platforms available in clinical and public health laboratories depend on reference databases that have not fully incorporated C. auris. Moreover, the correlation between minimal inhibitory concentration values (MICs) and clinical outcomes is poorly understood resulting in the absence of C. auris-specific breakpoints. New, accurate and fast diagnostic methods have emerged to facilitate effective patient management and improve infection control measures, ultimately reducing the potential for C. auris transmission. This review provides an overview of available C. auris detection/identification and antifungal susceptibility determination methods and discusses their advantages and limitations. A special emphasis has been placed on culture-independent methods that have recently been developed and offer faster turnaround times.